AI-based Digital Literacy for Vocational High School Principals in Muaro Jambi Regency - Rohayani, Hetty; Rico; Armiwita, Armiwita; Ermaini, Ermaini (Proletarian : Community Service Development Journal, 2024)
Digital transformation in education is increasingly important to create an innovative learning ecosystem. This article discusses the implementation of an artificial intelligence (AI)-based digital literacy program aimed at principals of Vocational High Schools (SMK) in Muaro Jambi Regency. The program aims to improve the principals' understanding and ability to utilize AI technology to support education and learning management. The activity methods involved workshops, simulations, and implementation of AI technologies. Results showed a significant improvement in principals' ability to integrate digital technology in school management. This article concludes the importance of AI-based digital literacy to strengthen principals' ability to face educational challenges in the digital era.